Paternal genetic effects of cadmium exposure during pregnancy on hormone synthesis disorders in ovarian granulosa cells of offspring - Yi Sun; Zhangpin Liu; Wenchang Zhang; Hao Lin; Qingyu Li; Chenchen Liu; Chenyun Zhang (BMC, 2023)
Abstract The aim of this study was to investigate the paternal genetic intergenerational and transgenerational genetic effects of cadmium (Cd) exposure during pregnancy on estradiol (E2) and progesterone (Pg) synthesis in the ovarian granulosa cells (GCs) of offspring. Pregnant SD rats were intragastrically exposed to CdCl2 (0, 0.5, 2.0, 8.0 mg/kg) from days 1 to 20 to produce the F1 generation, F1 males were mated with newly purchased females to produce the F2 generation, and the F3 generation was obtained in the same way. Using this model, Cd-induced hormone synthesis disorders in GCs of F1 have been observed [8]. In this study, altered serum E2 and Pg levels in both F2 and F3 generations showed a nonmonotonic dose‒response relationship. In addition, hormone synthesis-related genes (Star, Cyp11a1, Cyp17a1, Cyp19a1, Sf-1) and miRNAs were observed to be altered in both F2 and F3. No differential changes in DNA methylation modifications of hormone synthesis-related genes were observed, and only the Adcy7 was hypomethylated. In summary, paternal genetic intergenerational and transgenerational effects exist in ovarian GCs E2 and Pg synthesis disorders induced by Cd during pregnancy. In F2, the upregulation of StAR and CYP11A1, and changes in the miR-27a-3p, miR-27b-3p, and miR-146 families may be important, while changes in the miR-10b-5p and miR-146 families in F3 may be important.